P249 Comparison of physiological versus mathematical methods for quality control in mbw normalised phase iii analysis. (15th November 2016) - Arigliani, M; Verger, N; Raywood, E; Duncan, J; Bush, A; Aurora, P
Abstract : Background: Breathing pattern cannot be controlled in small children, so multiple breath washout SnIII analysis has to exclude inadequate volume breaths. Aim: To compare an existing mathematical breath exclusion algorithm with a physiological method. Methods: School age children with CF (30) and controls (30) performed SF6MBW with mass spectrometer, with uncontrolled tidal breathing. Two different breath exclusion methods were compared, with exclusion based on: 1) Expired tidal volume (VT) deviating by >25% of the median VT 1 2) VT <3 Langley dead space 2 volume or 90% bigger than the median VT Runs with >33% excluded breaths were removed. Volume corrected Scond was calculated from subjects with 3 valid runs. Results: Far fewer subjects were excluded by the physiological Langley method, than by the mathematical method (Table). The mean and SD for Scond was identical by both methods, implying that the mathematical algorithm excludes valid data. Conclusion: A physiological approach to data cleaning prior to SnIII analysis allows retention of data that would be inappropriately excluded mathematically. References: Bigler A, et al . Paediatric Pulmonol 2015;50 (8):805–13. Langley FE, et al . Colloques INSERM 1975;51 :209–212.